2008
DOI: 10.1161/circulationaha.107.741157
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Expressing Left Ventricular Mass Relative to Body Size in Children

Abstract: Background-Left ventricular (LV) hypertrophy (LVH) in children is widely defined as a left ventricular mass index (LVMI, g/m 2.7 ) Ͼ95th percentile. However, LVMI increases with decreasing height in young children; thus, the 95th percentile LVMI will depend on the height distribution of the reference population. The objective of this study was to compare the performance of a novel method of expressing LV mass relative to body size (centile curves) with the LVMI method. Methods and Results-LV mass was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 44 publications
2
156
0
13
Order By: Relevance
“…In analogy to the findings of Foster et al and Khoury et al in healthy children (14,15), we observed a significant inverse relationship of this LVMI with body size in children shorter than 130 cm. Although we cannot rule out the possibility of more marked LVH in young as compared with older children on dialysis, it is most likely that the Effect of reference to height age rather than chronological age on LVMI percentile assignment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In analogy to the findings of Foster et al and Khoury et al in healthy children (14,15), we observed a significant inverse relationship of this LVMI with body size in children shorter than 130 cm. Although we cannot rule out the possibility of more marked LVH in young as compared with older children on dialysis, it is most likely that the Effect of reference to height age rather than chronological age on LVMI percentile assignment.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Foster et al studied 440 healthy children and 239 children at risk of LVH (14). This single-center study was carefully standardized and a single cardiologist performed all measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LV reference mass of each heart for which heart weight was not available as the mean normal value for body surface area was calculated according to normal z-score values described in ref. 41. Our calculations were based on data from 576 healthy humans obtained at Boston Children's Hospital within an institutional review boardapproved study.…”
Section: Methodsmentioning
confidence: 99%